1992
DOI: 10.2337/diab.41.12.1540
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Factors Responsible for Glucose Intolerance in Patients With NIDDM

Abstract: To define the pathogenic factors responsible for glucose intolerance in NIDDM, we estimated insulin secretory capacity, SI, and SG in 11 healthy, nondiabetic subjects and 9 NIDDM patients who had no SI impairment. All subjects studied were nonobese and normotensive. Each underwent a 75-g OGTT and a modified FSIGT: glucose was administered (300 mg/kg body weight), and insulin was infused (20 mU/kg over 5 min) from 20 to 25 min after the administration of glucose. SI and SG were estimated by Bergman's minimal-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…Insulin secretion in Japanese individuals is reported to be less than half that of whites [16], [17], and most Japanese patients with type 2 diabetes do not have IR [18]. Additionally, studies in Sweden and those conducted in Pima Native Americans have shown that the acute insulin secretory response to intravenous glucose is an independent predictor of the development of diabetes [19][22].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin secretion in Japanese individuals is reported to be less than half that of whites [16], [17], and most Japanese patients with type 2 diabetes do not have IR [18]. Additionally, studies in Sweden and those conducted in Pima Native Americans have shown that the acute insulin secretory response to intravenous glucose is an independent predictor of the development of diabetes [19][22].…”
Section: Discussionmentioning
confidence: 99%
“…Using a minimal model, Welch et al (50) showed that S G as well as S I decreased in type 2 diabetes mellitus. Moreover, our previous reports (11,42,43) demonstrated that S G decreased in Japanese type 2 diabetic patients as well as in subjects with impaired glucose tolerance and type 2 diabetic offspring. Furthermore, an epidemiological study reported that a reduced S I and reduced S G are both strong predictors of type 2 diabetes mellitus (26).…”
mentioning
confidence: 85%
“…The ratio of adiponectin and leptin has also been reported to be associated with insulin resistance, which is considered to be one of the pathophysiological conditions underlying MetS [8, 9]. However, for instance, diabetes mellitus, a component of MetS, is not always caused by insulin resistance in Japanese people [10]. Furthermore, these earlier studies have not explored the association between L:A and MetS with regard to the determination of a potential cut-off level of L:A for detecting MetS and have not fully examined the L:A in the general community-dwelling population of Japan.…”
Section: Introductionmentioning
confidence: 99%